Strategi Komunikasi Pemasaran Dalam Upaya Membangun Brand Awareness Teh Kota Cabang Surakarta - Ardya Paramitha, Yovita Ruth; Hindra, Nurnawati; Widyowati, Estu (Solidaritas, 2024)
The trend of consuming tea in Indonesia continues to increase, especially in Surakarta City. Many Tea drink brands have sprung up and developed their own innovations to compete with other Tea drink brands. All promotions and offers are made, so that consumers recognize the product and are interested in buying the product. The emergence of a new brand of Teh Kota encouraged researchers to find out the role of marketing communication strategies in building brand awareness of Teh Kota Surakarta Branch. The theory used in this research is Promotion Mix. The method used in this research is descriptive qualitative. Data obtained from observations and interviews with informants, namely the owner, Barista, and three loyal consumers of Teh Kota Surakarta Branch. The results of this study describe that Teh Kota Surakarta Branch is in the Brand Recognition stage with the Promotion Mix strategy used is Advertising and Sales Promotion.